Talking Change - A comparative narrative analysis of language use amongst external consultants and internal change agents in delivering organisational change. - Muchatuta, Gashirai (2014)
This paper reports an investigation into the existence of material differences between the respective approaches to change management of consultants and corporate managers. The narrative accounts proffered by participants are examined in three primary dimensions, sensemaking, sensegiving and overcoming resistance to change. Relationships between these dimensions are explored and an effort at establishing best practice approaches is made.